The Highly Repeat-Diverse (Peri) Centromeres of White Lupin (Lupinus albus L.) - Marques, André; Hufnagel, Bárbara; Soriano, Alexandre; Péret, Benjamin (Frontiers in Plant Science, 2022)
Plant genomes are known to be mainly composed of repetitive DNA sequences. Regardless of the non-genic function of these sequences, they are important for chromosome structure and stability during cell cycle. Based on the recent available whole genome assembly of white lupin (Lupinus albus L.), we have in silico annotated and in situ mapped the main classes of DNA repeats identified with RepeatExplorer. A high diversity and abundance of satellite DNAs was found representing more than 10 families, where three of them are highly associated with CENH3-immunoprecipitated chromatin. Applying a strategy of several re-hybridization steps with different combinations of satDNA, rDNA and LTR-RTs probes we were able to construct of a repeat-based chromosome map for the identification of most chromosome pairs. Two families of LTR retrotransposons, Ty1/copia SIRE and Ty3/gypsy Tekay, were highly abundant at pericentromeric regions, while the centromeric retrotransposon of white lupin (CRWL) from the CRM clade showed strong centromere-specific localization in most chromosomes and was also highly enriched with CENH3-immunoprecipitated chromatin. FISH mapping of repeat DNA showed some incongruences with the reference genome, which can be further used for improving the current version of the genome. Our results demonstrate that despite the relatively small genome of white lupin a high diversity of pericentromeric repeats was found, emphasizing the rapid evolution of repeat sequences in plant genomes.